Speech Audiometry in Pakistan: Development of Urdu Spondee Words List (USWL) - Ijaz, Tehreem; Kiyani, Humaira Shamim; Saqulain, Ghulam (Annals of King Edward Medical University, 2023)
Background: Hearing impairment (HI) is a common barrier to communication which impacts the HI in achieving higher educational goals, impacts them at work and leisure and can result in social exclusion Objective: To developed Urdu Spondee Words List for establishing Speech Recognition Threshold in Urdu speaking hearing impaired population. Methods: This descriptive study was conducted in twin cities of Rawalpindi & Islamabad from July 2018 to January 2019. Study involved development of a tool called Urdu Spondee Word list (USWL) and familiarity judgement utilizing a sample of N=50 Urdu speaking participants of both genders aged 10-16 years utilizing convenience sampling, and finally voice analysis on PRATT software. SPSS version 21 was used for data analysis. Results: The results revealed that the final selected list of 18 spondee words has equally stressed syllables, with the accomplishment of the criteria of familiarity judgment for the participants. The recorded list shows minimum and maximum intensity variation of 3db to 8db in the homogenous audibility of the words making it suitable for speech recognition threshold measures. Conclusion: The developed 18 item Urdu Spondee Word list (USWL) with criteria of familiarity and homogenous audibility of words is suitable for speech recognition threshold measurement for Urdu speaking population.